Macrophages Facilitate Resistance to Anti-VEGF Therapy by Altered VEGFR Expression - Dalton, Heather J.; Pradeep, Sunila; McGuire, Michael; Hailemichael, Yared; MA, Shaolin; Lyons, Yasmin; Armaiz Pena, Guillermo N.; Previs, Rebecca A.; Hansen, Jean Marie; Rupaimoole, Rajesha; González Villasana, Vianey; Cho, Min Soon; et al. (2017)
Abstract Purpose: VEGF-targeted therapies have modest efﬁcacy in cancerpatients, butacquiredresistance iscommon. Themechanisms underlying such resistance are poorly understood. Experimental Design: To evaluate the potential role of immune cells in the development of resistance to VEGF blockade, we ﬁrst established a preclinical model of adaptive resistance to anti-VEGF therapy. Additional in vitro and in vivo studies were carried out to characterize the role of macrophages in such resistance. Results: Using murine cancer models of adaptive resistance to anti-VEGF antibody (AVA), we found a previously unrecognized roleofmacrophagesinsuchresistance.Macrophageswereactively recruited to the tumor microenvironment and were responsible for the emergence of AVA resistance. Depletion of macrophages following emergence of resistance halted tumor growth and prolonged survival of tumor-bearing mice. In a macrophagedeﬁcient mouse model, resistance to AVA failed to develop, but could be induced by injection of macrophages. Downregulation of macrophage VEGFR-1 and VEGFR-3 expression accompanied upregulation of alternative angiogenic pathways, facilitating escape from anti-VEGF therapy. Conclusions: These ﬁndings provide a new understanding of the mechanisms underlying the modest efﬁcacy of current antiangiogenesis therapies and identify new opportunities for combinationapproachesforovarianandothercancers. ClinCancerRes; 23(22); 7034–46. 2017 AACR.